Making Decisions About Stopping Medicines for Well‐Controlled Juvenile Idiopathic Arthritis: A Mixed‐Methods Study of Patients and Caregivers. Issue 3 (25th February 2021) - Horton, Daniel B.; Salas, Jomaira; Wec, Aleksandra; Kohlheim, Melanie; Kapadia, Pooja; Beukelman, Timothy; Boneparth, Alexis; Haverkamp, Ky; Mannion, Melissa L.; Moorthy, L. Nandini; Ringold, Sarah; Rosenthal, Marsha
Abstract : Objective: Improved treatments for juvenile idiopathic arthritis (JIA) have increased remission rates. We conducted this study to investigate how patients and caregivers make decisions about stopping medications when JIA is inactive. Methods: We performed a mixed‐methods study of caregivers and patients affected by JIA, recruited through social media and flyers, and selected by purposive sampling. Participants discussed their experiences with JIA, medications, and decision‐making through recorded telephone interviews. Of 44 interviewees, 20 were patients (50% ages <18 years), and 24 were caregivers (50% caring for children ages ≤10 years). We evaluated characteristics associated with high levels of reported concerns about JIA or medicines using Fisher's exact testing. Results: Decisions about stopping medicines were informed by competing risks between disease activity and treatment. Participants who expressed more concerns about JIA were more likely to report disease‐related complications ( P = 0.002) and more motivated to continue treatment. However, participants expressing more concern about medicines were more likely to report treatment‐related complications ( P = 0.04) and felt more compelled to stop treatment. Additionally, participants considered how JIA or treatments facilitated or interfered with their sense of normalcy and safety, expressed feelings of guilt and regret about previous or potential adverse events, and reflected on uncertainty and unpredictability of future harms. Decision‐making was also informed by trust in rheumatologists and other information sources (e.g., family and online support groups). Conclusion: When deciding whether to stop medicines whenever JIA is inactive, patients and caregivers weigh competing risks between disease activity and treatment. Based on our results, we suggest specific approaches for clinicians to perform shared decision‐making regarding stopping medicines for JIA.